2013
DOI: 10.1186/1477-7819-11-249
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study: the prognostic value of anemia, smoking and drinking in esophageal squamous cell carcinoma with primary radiotherapy

Abstract: BackgroundFew studies have investigated the relationship between anemia, smoking, drinking and survival in esophageal squamous cell carcinoma (ESCC) with primary radiotherapy. This study had the aim of evaluating the prognostic value of anemia, smoking and drinking in patients receiving primary radiotherapy for ESCC.MethodsA total of 79 patients who underwent radiotherapy during initial treatment for ESCC were included in this study. The 2-year overall survival (OS) and disease-free survival (DFS) were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…were similar to those of previous studies (Samadi et al, 2007;Kandaz et al, 2012;Schoppmann et al, 2013;Zhang et al, 2013).…”
Section: 3075 Lack Of Prognostic Value Of Bmi For Patients Undergoinsupporting
confidence: 93%
“…were similar to those of previous studies (Samadi et al, 2007;Kandaz et al, 2012;Schoppmann et al, 2013;Zhang et al, 2013).…”
Section: 3075 Lack Of Prognostic Value Of Bmi For Patients Undergoinsupporting
confidence: 93%
“…The prognostic value of the RDW/platelet ratio in myocardial infarction was also discussed [40, 41]. As HB is a well-established nutritional indicator and a potential prognostic factor in ESCC [16–19, 21, 22], we combined HB and RDW and built a novel prognostic index—the HB/RDW ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Low HB levels could reflect malnutrition in the host and the host immune status to some extent, both of which may indicate low tolerance to treatment. Several studies have demonstrated that anemia before treatment was a predictor of poor outcome in cancer patients, including patients with nasopharyngeal carcinoma, head and neck cancer, cervical cancer, ESCC and gastrointestinal cancer [16–19, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…We identified a total of 20 studies [9,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] which investigated the impact of smoking on survival in patients diagnosed with oesophageal cancer (Supplementary table 2). Most studies were singlecentred and focused on patients with oesophageal squamous cell carcinoma.…”
Section: Oesophageal Cancer Smoking and Survival In Oesophageal Cancementioning
confidence: 99%